DESIGN AND IN VITRO/IN VIVO EVALUATION OF EXTENDED RELEASE MATRIX TABLETS OF NATEGLINIDE - Sihare, Mohini; Chouksey, Rajendra (Journal of Biomedical and Pharmaceutical Research, 2018)
Aim: Nateglinide is a quick acting anti-diabetic medication whose potent activity lasts for a short duration. One of the dangerous side effects of nateglinide administration is rapid hypoglycemia, a condition that needs to be monitored carefully to prevent unnecessary fatalities. The aim of the study was to develop a longer lasting and slower releasing formulation of nateglinide that could be administered just once daily.Methods: Matrix tablets of nateglinide were prepared in combination with the polymers hydroxypropylmethylcellulose (HPMC), eudragits, ethyl cellulose and polyethylene oxide and the formulated drug release patterns were evaluated using in vitro and in vivo studies.Conclusion: Of the seventeen formulated matrix tablets tested, only one formulation labelled HA-2 that contained 15% HPMC K4M demonstrated release profile we had aimed for. Further, swelling studies and scanning electron microscopic analysis confirmed the drug release mechanism of HA-2. The optimized formulation HA-2 was found to be stable at accelerated storage conditions for 3 months with respect to drug content and physical appearance. Mathematical analysis of the release kinetics of HA-2 indicated a coupling of diffusion and erosion mechanisms. In-vitro release studies and pharmacokinetic in vivo studies of HA-2 in rabbits confirmed the sustained drug release profile we had aimed for.Keywords: Hydroxypropylmethylcellulose, Matrix tablets, Nateglinide, Sustained release